Corpus-driven lexical analyses of CorCel: a comparative analysis of preliminary findings of written proficiency in Portuguese as an additional language - Stumpf, Elisa Marchioro; Schoffen, Juliana; Divino, Luiza Sarmento; Hanauer, Isadora Dahmer; Raupp, Amanda; Xavier, Brenda (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2025: Anais do XVI Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana, 2025)
This paper aims to comparatively analyze research on CorCel [Schoffen et al. , forthcoming] a corpus of written texts produced under exam conditions for the Celpe-Bras exam. It compares studies that examined tasks using Sketch Engine’s keywords, wordlist, n-grams and concordance tools. These studies also analyzed text length and lexical richness using lexical diversity indices. The comparative study showed relevant lexical indexes for characterizing the exam proficiency levels, such as text length, and important differences in the use of input material and other linguistic resources among texts rated with different grades. Such analyses offer new possibilities for research in Portuguese as an additional language (PAL) proficiency assessment and teaching.